2018
DOI: 10.1159/000486104
|View full text |Cite
|
Sign up to set email alerts
|

The<b><i> IL20</i></b> Genetic Polymorphism Is Associated with Altered Clinical Outcome in Septic Shock

Abstract: Background: The IL10 family of genes includes crucial immune regulators.We tested the hypothesis that single nucleotide polymorphisms (SNPs) in IL10, IL19, IL20, and IL24 of the IL10 family gene cluster alter the clinical outcome of septic shock. Methods: Patients with septic shock (n = 1,193) were genotyped for 13 tag SNPs of IL10, IL19, IL20, and IL24. IL20 gene expression was measured in genotyped lymphoblastoid cells in vitro. Cardiac surgical ICU patients (n = 981) were genotyped for IL20 rs2981573 A/G. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In another study dealing with a clinical aspect of sepsis, Jon Olinder and co-workers [4] found that hepcidin, a peptide hormone controlling plasma levels of iron, can be used as a diagnostic tool in patients suffering from severe infectious diseases. These two contributions are in line with other recently published articles in Journal of Innate Immunity demonstrating that deciphering molecular mechanisms causing severe complications in infectious diseases can lead to novel concepts in diagnosis and treatment [5][6][7][8][9]. The immunomodulation in sepsis and septic shock shares similarities with other diseases, such as chronic obstructive pulmonary disease and cystic fibrosis [10][11][12].…”
supporting
confidence: 81%
“…In another study dealing with a clinical aspect of sepsis, Jon Olinder and co-workers [4] found that hepcidin, a peptide hormone controlling plasma levels of iron, can be used as a diagnostic tool in patients suffering from severe infectious diseases. These two contributions are in line with other recently published articles in Journal of Innate Immunity demonstrating that deciphering molecular mechanisms causing severe complications in infectious diseases can lead to novel concepts in diagnosis and treatment [5][6][7][8][9]. The immunomodulation in sepsis and septic shock shares similarities with other diseases, such as chronic obstructive pulmonary disease and cystic fibrosis [10][11][12].…”
supporting
confidence: 81%
“…Our primary analysis used Cox regression to test for hazard of death over 90 days by the vital signs in the elderly and non-elderly groups. We selected this approach to adjust for potential baseline imbalances, including age (per year), sex, chronic steroid use, and APACHE II score (Additional file 1: Table S2, correlation analysis) based on previous reports [18,23]. Significant discovery results were tested for replication and generalizability in patients of the same ancestry in validation cohort 1 and patients of different ancestry in validation cohort 2.…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments are required in order to analyze the epithelial permeability in a model of air–liquid interface after viral infection and the role of IL-20 cytokines. Moreover, it has been shown that some polymorphism in IL-19 and IL-20 genes could worsen the outcome of chronic hepatitis B infection [ 14 ] and septic shock [ 40 ]. IL-20 cytokines may be a common link between these diseases.…”
Section: Discussionmentioning
confidence: 99%